Clays and Clay Minerals, Vol. 58, No. 5, 721–723, 2010. - Nieto, Fernando; Mellini, Marcello; Abad, Isabel (The Clay Minerals Society, 2010)
The arguments of Vidal et al. (2010) against the incorporation of H3O+ rather than of H2O in the interlayer position of illite are disputable. Stoichiometric arguments do indeed suggest that the excess water in the Silver Hill illite is in the formof H3O+. No reason exists to assume less water content in the IMt-2 sample than in those determined by Hower and Mowatt (1966) and confirmed by the thermogravimetric analyses of Nieto et al. (2010). The comparison between element contents calculated from end-members and those from the structural formula in figure 1 of Vidal et al. (2010) is not an experimental result, but rather a trivial mathematical artifact. The fact that thermodynamic models, based on the incorporation of interlayer H2O in illite, may provide reasonable estimates neither proves nor disproves the presence of H3O+; this is because thermodynamics is a non-atomistic, macroscopic approach.
Reply To The Comment By Vidal, Dubacq, And Lanari On ‘‘the Role Of H3o+ In The Crystal Structure Of Illite’’
gsccm58511-rep.pdf --77KB
Keywords: Periodicals; Geology; Composition; Hydronium; Illite; Water